2018
DOI: 10.1080/16070658.2018.1448503
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition among children under five in the Bandja village of Cameroon, Africa

Abstract: Sub-Saharan Africa has a long history of struggling with child undernutrition. The prevalence of undernutrition is still high and knowledge about this public health problem and the underlying causes is essential for children's health. Aim: To evaluate the anthropometric status of children under five in the Bandja village of Cameroon. Methods: A cross-sectional study was undertaken that included 388 children. Undernutrition was evaluated in terms of wasting, stunting and underweight. Information on sex, age, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 12 publications
3
15
2
1
Order By: Relevance
“…Age has a positive association with the underweight of under five children and children in higher age groups had higher odds of underweight. Which is consistent with the finding of [ 8 10 ]. This finding shows that later age within under 5 years’ age carry a higher risk of underweight.…”
Section: Discussionsupporting
confidence: 94%
“…Age has a positive association with the underweight of under five children and children in higher age groups had higher odds of underweight. Which is consistent with the finding of [ 8 10 ]. This finding shows that later age within under 5 years’ age carry a higher risk of underweight.…”
Section: Discussionsupporting
confidence: 94%
“…Birth interval was found significantly associated with SAM in bivariate analysis of our study but upon adjusting confounders in multivariate analysis, it was not significantly associated with SAM. In accordance with our study, a study done in Africa has also found birth interval to be insignificantly associated with SAM [40]. Other driving factors like poor economic condition of the household might have impacted more on the occurrence of SAM, therefore, birth interval was found to be insignificant with SAM.…”
Section: Discussionsupporting
confidence: 90%
“…Other risk factors also include poor maternal nutrition and low birth weight. However, magnitude of these risk factors varies from one locality to another [ 9 , 12 ]. Using an unmatched case-control study, we aimed to determine the risk factors associated with undernutrition among children under-five years of age living in Ngorongoro district.…”
Section: Introductionmentioning
confidence: 99%